2015
DOI: 10.1111/ajt.13316
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Platelet Activation and Hypercoagulability by Antithymocyte Globulins (ATG)

Abstract: T cell depletion with antithymocyte globulins (ATG) can be complicated by thrombopenia and hypercoagulability. The underlying mechanism is still unclear. We found that binding of ATG to platelets caused platelet aggregation, a-granule release, membrane phosphatidylserine exposure and the rapid release of procoagulant platelet microvesicles (MV). Platelet activation and MV release were complement-dependent and required membrane insertion of C5b-8 but not stable lytic pore formation by C5b-9. ATG also activated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…Furthermore, C3 levels have been associated with sclerotic cutaneous GVHD patients (106) and patients with sclerotic GVHD have shown abnormalities in complement factor H and APC functional assays (107). Complement activation has been also linked with thrombin generation in patients treated with antithymocyte globulins (ATG) (108).…”
Section: Transplant-associated Tmamentioning
confidence: 99%
“…Furthermore, C3 levels have been associated with sclerotic cutaneous GVHD patients (106) and patients with sclerotic GVHD have shown abnormalities in complement factor H and APC functional assays (107). Complement activation has been also linked with thrombin generation in patients treated with antithymocyte globulins (ATG) (108).…”
Section: Transplant-associated Tmamentioning
confidence: 99%
“…demonstrated ATG also binds and depletes platelets in a complement dependent manner. 48 Ayuk et al. suggested that ATG also causes caspase-dependent cell death, but that this was complement-independent.…”
Section: Discussionmentioning
confidence: 99%
“…Anti‐thymocyte globulin (ATG) is used in the management of patients with aplastic anaemia (AA) and hypoplastic myelodysplastic syndrome (H‐MDS). Administration of ATG causes significant thrombocytopenia due to non‐specific binding of platelets resulting in activation and degranulation (Cumpelik et al , ). In the recently published AA guidelines, the British Committee for Standards in Haematology (BCSH) provides guidance on ATG therapy and platelet count thresholds (Killick et al , ).…”
mentioning
confidence: 99%
“…Bleeding may have been mitigated in our patients with prophylactic tranexamic acid. ATG is known to be associated with an increase in tissue factor and thrombin‐antithrombin complexes, however it has not correlated with bleeding or thromboembolic manifestations (Weber et al , ; Inbal et al , ; Cumpelik et al , ).…”
mentioning
confidence: 99%